PENGARUH SEGMENTASI TARGETING DAN POSITIONING TERHADAP PENINGKATAN VOLUME PENJUALAN MOBIL MEREK PAJERO SPORT DI PT. BOSOWA BERLIAN MOTOR KOTA MAKASSAR - Burhanuddin; Muh. Ichwan Musa; Romansyah Sahabuddin; Zainal Ruma; Basri (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effect of segmentation, targeting and positioning on increasing sales volume. The data collection technique was carried out by means of interviews and questionnaires to consumers who bought Pajero sports cars at PT. Bosowa Berlian Motor, Makassar City, with a population of 227 people and a sample of 70 people. The method used is multiple linear regression using the SPSS application. The test used in this research is instrument test. Based on the results of this study using multiple linear regression analysis, the regression equation Y= 17.331+0.475.X1+(-0.365).X2+0.288.X3+e. The indicators in this study are valid and the variables are reliable. As for the classical assumption, it is said that all indicators are declared normally distributed and have a significant linear correlation value between each independent variable and the dependent variable, on the magnitude of the influence of Segmentation, Targeting and Positioning each of which has a positive direction and some are negative as well as significant in its influence on the increase in sales volume of Mitsubishi Pajero Sport brand cars at PT. Bosowa Berlian Motor Makassar City.